Pendidikan yang Berkeadilan: Menakar Mutu Pembelajaran Berbasis Teknologi di Masa Pandemi Covid-19 - Fabianus Selatang; Adison Adrianus Sihombing (ISJN Journal, 2021)
One of the fundamental problems that undermine education during the pandemic Covid-19 is quality educational services that are accessible to all students. Quality education services relating to issues of ownership and control technology. The use of digital technology with accessibility, connectivity, and flexibility is often seen as a learning solution during a pandemic. This perception is mistaken when used for understanding reality. Educational services limitation and lack of understanding in learning application/platform is a problem that is still concerning for teachers, students, and parents. This has an impact on the formulation of problem-solving action plans that are faced during a pandemic. This paper aims to show the other side of those perceptions that can be perceived as an opportunity and also a challenge. The method used in this research is the qualitative method with a descriptive approach. The type of research is library research. The author collected relevant library data. Data was collected in form of both national and international journal articles reviewing education and the impact of a pandemic on the education system. Collected data were analyzed using restatement, description, and interpretation stages. The result of this research shows that learning difficulties tend to be caused by the lack of technology-based learning essence. This result also takes effect on mindset-changing attitude, paradigm, and viewpoint towards learning reality during Covid-19 pandemics. Finally, learning during the Covid-19 pandemic reflects two things: First, learning practices must be relevant, futuristic, responsive to the context of the times. Second, socio-cultural transformation becomes a precondition for a system change in the learning process so that education takes root and becomes a new tradition that applies in society and becomes best practices.With this understanding, not only pandemic reality can be contextually well-understood but also problem-solving actions can be formulated precisely.